140k views
2 votes
3a^2 -3a - 36. solving quadratic by factoring. factor each expression. be sure to check for greatest common factor first.

User Sai Z
by
5.0k points

1 Answer

0 votes

we have the expression


3a^2-3a-36

step 1

Factor 3


3(a^2-a-12)

step 2

equate to zero


3(a^2-a-12)=0

step 3

Solve


(a^2-a-12)=0
\begin{gathered} a^2-a=12 \\ (a^2-a+(1)/(4)-(1)/(4))=12 \\ (a^2-a+(1)/(4))=12+(1)/(4) \\ (a^2-a+(1)/(4))=(49)/(4) \end{gathered}

Rewrite as perfect squares


(a-(1)/(2))^2=(49)/(4)

take the square root on both sides


\begin{gathered} a-(1)/(2)=\pm(7)/(2) \\ a=(1)/(2)\pm(7)/(2) \end{gathered}

the values of a are

a=4 and a=-3

therefore


3(a^2-a-12)=3(a-4)(a+3)

User Guillem
by
5.6k points